2020
DOI: 10.1109/tap.2020.2969888
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost Nonuniform Metallic Lattice for Rectifying Aperture Near-Field of Electromagnetic Bandgap Resonator Antennas

Abstract: This paper addresses a critical issue, which has been overlooked, in relation to the design of Phase Correcting Structures (PCSs) for Electromagnetic Bandgap (EBG) Resonator Antennas (ERAs). All previously proposed PCSs for ERAs are made either using several expensive Radio Frequency (RF) dielectric laminates, or thick and heavy dielectric materials, contributing to very high fabrication cost, posing an industrial impediment to the application of ERAs. This paper presents a new industrialfriendly generation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
52
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 31 publications
0
52
0
Order By: Relevance
“…A FSS meta‐surface is used to reduce the RCS of a wideband circularly polarized fabry‐perot cavity antenna 25 . Phase‐correcting structures employing all‐dielectric materials 26,27 and all‐metal structures 28 have been used for phase‐error elimination. Recently artificial intelligence‐based approaches, such as particle swarm optimization 29‐31 have been used to design near‐field correction structures.…”
Section: Introductionmentioning
confidence: 99%
“…A FSS meta‐surface is used to reduce the RCS of a wideband circularly polarized fabry‐perot cavity antenna 25 . Phase‐correcting structures employing all‐dielectric materials 26,27 and all‐metal structures 28 have been used for phase‐error elimination. Recently artificial intelligence‐based approaches, such as particle swarm optimization 29‐31 have been used to design near‐field correction structures.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the satellite communications industry has created a demand for low-mass narrowband low-loss filters with high selectivity [13][14][15]. As a result, affordability and compactness have become two critical requirements of microwave filters and other electromagnetic components used in the upcoming new generation of low-cost Satcom systems, where satellite communication-on-the-move will become a part of everyday life [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Working as a spatial filter, traditional frequency selective surface (FSS) is constituted by an infinite array of metallic patterns printed on a dielectric substrate to control the transmission and reflection of an incident electromagnetic wave [1]. Additionally, it is reported that FSSs can be made of different materials, like all-dielectric materials [2], printed surfaces [3], or all metal structures [4]. Since natural materials do not possess the characteristic of frequency selectivity, FSS is also classified as the concept of metasurface by some scholars, which has gained a lot of attention over the past decade [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%